2015
DOI: 10.1002/anie.201504731
|View full text |Cite
|
Sign up to set email alerts
|

A Crystal Structure of a Functional RNA Molecule Containing an Artificial Nucleobase Pair

Abstract: As one of its goals, synthetic biology seeks to increase the number of building blocks in nucleic acids. While efforts towards this goal are well advanced for DNA, they have hardly begun for RNA. Herein, we present a crystal structure for an RNA riboswitch where a stem C:G pair has been replaced by a pair between two components of an artificially expanded genetic-information system (AEGIS), Z and P, (6-amino-5-nitro-2(1H)-pyridone and 2-amino-imidazo[1,2-a]-1,3,5-triazin-4-(8H)-one). The structure shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Utilizing DNA as a material building block in molecular and structural engineering has already led to the creation of numerous molecular-assembly systems and materials at the nanoscale [ 19 ]. Substantial efforts have been made to expand the genetic alphabet of DNA by introducing other base pair combinations, so-called unnatural base pairs ( UBP ) to increase nucleic acid functionalities [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Recently, modifications of DNA containing four NBP and four additional UBP which efficiently replicated [ 32 , 32 ] were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing DNA as a material building block in molecular and structural engineering has already led to the creation of numerous molecular-assembly systems and materials at the nanoscale [ 19 ]. Substantial efforts have been made to expand the genetic alphabet of DNA by introducing other base pair combinations, so-called unnatural base pairs ( UBP ) to increase nucleic acid functionalities [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Recently, modifications of DNA containing four NBP and four additional UBP which efficiently replicated [ 32 , 32 ] were reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, introduction of a single Z:P pair into the stem of an RNA riboswitch marginally increased the stability of that stem; a crystal structure showed essentially no geometric perturbation (Fig. 7, right) (Hernandez et al 2015). In DNA, the crystal structure of a single Z:P pair likewise shows no substantial deviation from Watson -Crick geometry (Zhang et al 2015) (Fig.…”
Section: Nucleobase Pairing Is Constructively As Simple As the Watsonmentioning
confidence: 96%
“…A 16-mer duplex with six consecutive Z:P pairs (center)(Georgiadis et al 2015). A single Z:P pair in an RNA riboswitch in four views A, B, C, and D each rotated 90˚(right)(Hernandez et al 2015).…”
mentioning
confidence: 99%
“…These biophysical studies were followed by crystallographic studies that showed that AEGIS components do, in fact, pair with Watson–Crick geometry. For example, the introduction of a single Z:P pair into the stem of a riboswitch marginally increased the stability of that stem; a crystal structure showed essentially no geometric perturbation [ 92 ] ( Figure 2 , right). In DNA, the crystal structure of a single Z:P pair likewise showed no substantial deviation from Watson–Crick geometry [ 93 ].…”
Section: The Artificially Expanded Genetic Information System (Aegmentioning
confidence: 99%
“… Crystal structures with Z:P AEGIS pairs: ( left ) A 16-mer duplex with six consecutive Z:P pairs [ 82 ]; ( right ) A single Z:P pair containing a RNA guanine riboswitch superimposed to its natural counterpart [ 92 ]. …”
Section: Figurementioning
confidence: 99%